2016
DOI: 10.1080/13803395.2016.1198469
|View full text |Cite
|
Sign up to set email alerts
|

Self-awareness of cognitive efficiency: Differences between healthy elderly and patients with mild cognitive impairment (MCI)

Abstract: The present results indicate that accuracy of self-report is not uniform across groups and functional areas. The discrepancies in the MCI patients indicate unawareness of their memory deficits, which is contradictory to subjective memory complaints as being an important component for clinical diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 58 publications
3
30
1
2
Order By: Relevance
“…Specifically, with respect to depression or subclinical mood changes, future research is needed to better understand the mechanisms associated with the relationship between familial risk and declines in brain health. Although our examination of the subjective impairment is less susceptible to the effects of hyper- or anosognosia of memory decline 35,37 when compared with a dichotomous assessment, 21 multi-item scales would allow further differentiation of subjective cognitive deficits beyond memory.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, with respect to depression or subclinical mood changes, future research is needed to better understand the mechanisms associated with the relationship between familial risk and declines in brain health. Although our examination of the subjective impairment is less susceptible to the effects of hyper- or anosognosia of memory decline 35,37 when compared with a dichotomous assessment, 21 multi-item scales would allow further differentiation of subjective cognitive deficits beyond memory.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this information refers to the functioning of self-awareness in general, not related to a specific task (in an offline fashion), although they refer to the functioning of the subject in his natural environment, theoretically with greater ecological validity. The third modality, mainly used in experimental studies dealing with meta-cognition, is based on the quantification of the accuracy of the subject in judging previously or after his performance to a standardized neuropsychological task (typically memory or executive functions) and comparing it with its actual performance (Fragkiadaki et al, 2016). This methodology has the undoubted advantage of being able to have an online quantification of the subject’s self-awareness, but at the same time, the used tasks and the traditional neuropsychological tests are useful for evaluating specific cognitive domains and deficient in an ecological evaluation of functional abilities.…”
Section: Self-awareness In Neurodegenerative Disordersmentioning
confidence: 99%
“…In a study by Galeone et al (12), global prediction of recall performance before and after study was found to be less accurate in aMCI patients compared to controls. MCI patients also overestimated their cognitive performance in various tasks including memory during post-test ratings (28). In contrast, Clare et al (25) found that MCI patients were as good as controls in the rating of their performance in the Rivermead Behavioral Memory Test after each subtest completion.…”
Section: Introductionmentioning
confidence: 95%